Method for producing metal-organic framework composites

Dip-coating organometallic framework powder onto a monolith in a liquid suspension maintains the high surface area and porosity of organometallic frameworks, addressing brittleness and processability issues, enabling their use in adsorbent beds and reactors.

JP7611928B2Active Publication Date: 2025-01-10EXXONMOBIL TECHNOLOGY & ENGINEERING CO
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022552658
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-04
Filing Date
2021-01-19
Publication Date
2025-01-10
Estimated Expiration
2041-01-19

AI Technical Summary

Technical Problem

Existing methods for producing organometallic frameworks suffer from brittleness and poor processability, leading to reduced surface area and porosity when shaped into devices, and conventional processing techniques are not applicable due to insolubility in solvents.

Method used

A method involving dip-coating organometallic framework powder onto a monolith in a liquid suspension, followed by drying, to create a composite with maintained surface area and porosity, using specific conditions to ensure structural integrity and functional properties.

Benefits of technology

The method preserves the high surface area and porosity of organometallic frameworks, enabling their use in adsorbent beds and reactors with improved structural integrity and functional properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007611928000001
    Figure 0007611928000001
  • Figure 0007611928000002
    Figure 0007611928000002
  • Figure 0007611928000003
    Figure 0007611928000003
Patent Text Reader

Abstract

Provided herein is a method for producing an adsorbent bed useful as a microreactor or catalytic and / or separation device. The adsorbent bed comprises a metal-organic framework composite. In this method, one or more metal-organic frameworks in powder form are mixed in a liquid to produce a metal-organic framework suspension or other type of metal-organic framework coating. A monolith is coated with the suspension or coating to provide a metal-organic framework composite having at least one metal-organic framework coating layer deposited on and bordering the monolith. The metal-organic framework composite produced has a thickness of about 1 m. 2 / g~about 300m 2 / g and / or a relative BET surface area of ​​about 40% to about 100% with respect to the metal-organic framework monolith, and a pore diameter of about 1 nm to about 50 nm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates generally to the formulation of metal-organic frameworks, and in particular to a method for making a metal-organic framework composite having at least one metal-organic framework coating layer deposited on a monolith. [Background technology]

[0002] For adsorption applications, materials with large internal surface areas defined by pores and channels are advantageous. A method for making such microporous or mesoporous active materials includes the use of metal-organic frameworks. Metal-organic frameworks offer several advantages over other types of materials, such as significant porosity and internal surface areas, high surface-to-volume ratios, and excellent separation and catalytic performance and fluid storage. Furthermore, the pore size and channel structure of metal-organic frameworks can be tuned over a large range. Furthermore, metal-organic frameworks can be easily functionalized.

[0003] Despite these advantages, proper formulation of metal-organic frameworks is important for various applications. Previous methods include synthesizing metal-organic frameworks in powder form and shaping the powder into, for example, membranes, thin films, pellets, monoliths, and foam precursors for industrial applications. However, these devices are significantly adversely affected by their inherent brittleness and poor processability. Furthermore, unlike organic polymers, metal-organic framework crystals are insoluble in any solvent and are usually not thermoplastic, meaning that traditional solvent-based or melt-based processing techniques are not applicable to metal-organic frameworks. Recently, direct ink writing (3D printing) of high-purity metal-organic framework monoliths has been proposed. However, the main challenge of this method is that the material must be made into a suspension with ideal rheological properties, capable of flowing continuously through fine nozzles without clogging (shear thinning). Summary of the Invention [Problem to be solved by the invention]

[0004] Thus, there is a need for methods of fabricating metal-organic framework devices that can maintain the structural integrity of metal-organic frameworks without reducing the surface area and porosity advantages that such materials offer. [Means for solving the problem]

[0005] A method of producing an adsorbent bed comprising the steps of: (a) mixing a metal-organic framework in powder form into a liquid to produce a suspension; (b) providing a monolith; (c) dip-coating the monolith in the suspension to produce a metal-organic framework composite having at least one metal-organic framework coating layer deposited on and bordering the monolith; and (d) drying the metal-organic framework composite to produce a monolith having a thickness of about 5 m. 2 / g~about 100m 2 and producing an absorbent bed having a BET surface area of ​​about 100 nm to about 50 nm.

[0006] Also provided herein is a method of producing an adsorbent bed, comprising the steps of: (a) mixing a metal-organic framework in powder form in a liquid to produce a suspension; (b) providing a monolith; (c) dip-coating the monolith in the suspension to produce a metal-organic framework composite having at least one metal-organic framework coating layer deposited on and bordering the monolith; and (d) drying the metal-organic framework composite to produce an adsorbent bed having a relative BET surface area of ​​about 1% to about 10% relative to the metal-organic framework monolith and a pore size in the metal-organic framework of about 1 nm to about 50 nm, wherein the adsorbent bed has micropores.

[0007] A method for producing a metal-organic framework composite useful as an adsorbent bed, comprising the steps of: (a) suspending a metal-organic framework powder in a liquid to produce a suspension, wherein the metal-organic framework powder is about 10 wt % to about 90 wt % of the suspension, and the suspension is acid-free; (b) casting the suspension onto a substrate to produce a metal-organic framework composite comprising a metal-organic framework coating deposited on the monolith; and (c) heating the metal-organic framework composite with one or more zeolites to adhere a metal-organic framework coating to the monolith, wherein the metal-organic framework composite has a thickness of about 5 μm. 2 / g~about 100m 2 / g and / or a relative BET surface area of ​​about 1% to about 10% relative to the metal-organic framework monolith, and a pore size of about 1 nm to about 50 nm.

[0008] Further, a method of producing a metal-organic framework composite includes the steps of: (a) mixing a metal-organic framework powder with a liquid to form a metal-organic framework coating; (b) applying the metal-organic framework coating to a monolith by thermal deposition to produce a metal-organic framework composite, the metal-organic framework coating comprising a weight percent (wt%) of the metal-organic framework in the liquid ranging from about 30 wt% to about 60 wt%; and (c) drying the metal-organic framework composite at a temperature less than 250° C. to obtain a metal-organic framework having a thickness of about 500 nm. 2 / g~about 100m 2 and producing a metal-organic framework composite having a BET surface area of ​​about 100 nm to about 200 nm / g and / or a relative BET surface area of ​​about 1% to about 10% relative to the metal-organic framework monolith, and a pore size of about 2 nm to about 50 nm.

[0009] In an embodiment, the metal-organic framework is HKUST-1, the liquid is ethanol, and the monolith is alumina washcoated cordierite. In an embodiment, the metal-organic framework is Mg-MOF-74, the liquid is ethanol, and the monolith is ceramic. In an embodiment, the method further comprises aging the metal-organic framework composite at a temperature of about 40° C. to about 150° C. for a period of about 30 minutes or more. In an embodiment, the method further comprises calcining the metal-organic framework composite at a temperature of about 100° C. to about 300° C. for a period of about 1 hour or more. In an embodiment, the method further comprises washing the metal-organic framework composite with an optional solvent. In an embodiment, the optional solvent is selected from the group of water, methanol, ethanol, dimethylformamide, acetone, diethyl ether, acetonitrile, ketones, amides, esters, ethers, nitriles, aromatic hydrocarbons, aliphatic hydrocarbons, and combinations thereof. In an embodiment, the adsorbent bed is a channel reactor for gas and fluid.

[0010] In an embodiment, the monolith is selected from the group of ceramic, metal, polymeric substrate and / or cellulose fiber. In an embodiment, the monolith is ceramic. In an embodiment, the polymeric substrate comprises polyvinylamide, polyacrylate, polycarbonate, polyamide, polyester, polyether, polyvinylamine, polyvinyl alcohol, polyvinyl ester and / or combinations thereof.

[0011] In an embodiment, the metal-organic framework is selected from the group of HKUST-1, UiO-66, ZIF-8, ZIF-7, MIL-100, MOF-74, M2(m-dobdc), MOF-274, Cu(Qc)2, and combinations thereof.

[0012] Deposited on the monolith and bordering it, approximately 5 m 2 / g~about 200m 2Further provided herein is a channel reactor for gases and fluids comprising at least one layer of a metal-organic framework coating that results in a metal-organic framework composite having a BET surface area of ​​about 1000 nm / g and / or a relative BET surface area of ​​about 1% to about 10% relative to the metal-organic framework monolith and a pore size of about 1 nm to about 50 nm. In an embodiment, the monolith of the channel reactor is cordierite. In an embodiment, the cordierite is washcoated with alumina. In an embodiment, the monolith of the channel reactor is primarily alumina. [Brief description of the drawings]

[0013] [Figure 1A] 1 is a photographic image of a 400 cpsi square channel forming monolith of ceramic material coated with a formulated HKUST-1 metal-organic framework coating. [Figure 1B] 1 is a photographic image of a 400 cpsi square channel forming monolith of ceramic material coated with a formulated HKUST-1 metal-organic framework coating. [Diagram 2] 1 is a micrograph of a monolith of ceramic material with square channels coated with Mg-MOF-74. [Diagram 3] 1 shows a micrograph of the ceramic monolith before coating. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Before describing in more detail the methods of fabricating the metal-organic framework composites of the present disclosure, a list of terms follows to aid in a better understanding of the present disclosure.

[0015] All numerical values ​​within the detailed description and claims herein are modified by "about" or "approximately" with respect to the indicated value to account for experimental error and variations that would be expected by one of ordinary skill in the art. Unless otherwise specified, room temperature is about 25°C.

[0016] For simplicity, only certain ranges are expressly disclosed herein.However, a range from any lower limit can be combined with any upper limit to recite a range that is not expressly recited, and a range from any lower limit can be combined with any other lower limit to recite a range that is not expressly recited, and similarly, a range from any upper limit can be combined with any other upper limit to recite a range that is not expressly recited.Furthermore, a range includes any point or single value between its endpoints, even if not expressly recited.Therefore, any point or single value can be combined with any other point or single value or any other lower limit or upper limit to become its own lower limit or upper limit, and can recite a range that is not expressly recited.

[0017] As used in this disclosure and the claims, the singular forms "a," "an," and "the" include the plural forms unless the context clearly dictates otherwise.

[0018] As used herein, the term "and / or" in phrases such as "A and / or B" is intended to encompass "A and B," "A or B," or "A" and "B."

[0019] The term "aqueous medium" means a liquid containing 5% or more by volume of water. Suitable aqueous media can comprise or consist essentially of water or a mixture of water and a water-miscible organic solvent.

[0020] The term "pre-crystallized" refers to materials, particularly metal-organic framework materials, that are synthesized in advance (pre-formed) and that are typically separated from the reaction medium in which they are formed.

[0021] As used herein, the term "metal-organic framework material" or "MOF material" refers to a metal or metalloid and an organic ligand capable of coordinating to the metal or metalloid. In certain embodiments, the MOF coordination network of the organic ligand and the metal (or metalloid) forms a porous three-dimensional structure.

[0022] In general, metal-organic frameworks (MOFs) are a class of highly porous materials that have promising applications in a wide range of fields, including gas storage, gas and liquid separation, isomer separation, waste removal, and catalysis, among others. In contrast to zeolites, which are purely inorganic in nature, MOFs utilize organic ligands that can function as "pillars" bridging metal atoms or clusters of metal atoms together. Like zeolites, MOFs are microporous. The pore shape and size of MOFs can be tailored by the choice of organic ligands and metals. The organic ligands can be modified, so that MOFs as a whole are structurally diverse, unlike zeolites. Factors that affect the structure of MOFs include, for example, one or more of the following: the number of coordination sites of the ligands, the size and type of the coordination groups, additional substitutions distant from or adjacent to the coordination groups, the size and shape of the ligands, the hydrophobicity or hydrophilicity of the ligands, the choice of metal and / or metal salt, the choice of solvent and reaction conditions, such as temperature, concentration, etc.

[0023] MOFs are synthesized or commercially obtained as crystalline powder materials. As described above, for many industrial and commercial products, MOFs in powder form can be shaped into larger aggregates with defined shapes that may be desirable. Conventional methods of consolidating MOFs in powder form into larger objects, such as pelleting and extrusion, often result in less than desirable physical and mechanical properties. More specifically, processing MOFs in powder form by compaction can result in smaller BET surface areas than MOFs in powder form due to the pressure sensitivity and relatively low crush strength of the MOF structures. Furthermore, certain processing conditions can result in complete or partial phase transformation of the initial MOF structures, as shown by x-ray powder diffraction and BET surface area analysis. Each of these factors can be problematic for producing MOFs in the form of shaped bodies and / or for using the shaped bodies as devices in various applications.

[0024] Although it is desirable to consolidate metal-organic framework ("MOF") powders into more cohesive (shaped) objects, the properties of MOFs, specifically their susceptibility to pressure and shear, can lead to various problems under the pressures (e.g., from about 100 psi to several thousand psi) and shear used to consolidate powder-form MOFs, especially during extrusion. Such processing of MOF powders can collapse at least some of the pores in the MOF structure, resulting in an undesirable and often significant reduction in BET surface area. Furthermore, the conditions used to consolidate powder-form MOFs into shaped objects can result in at least partial, and sometimes complete, conversion of the MOF structure to another material, such as another crystalline phase. Consolidated MOFs with insufficient crush strength can be problematic. For example, insufficient crush strength values ​​can produce fine grains, which may not be desirable for certain applications.

[0025] Provided herein is a method for producing an adsorbent bed useful as a microreactor or catalytic and / or separation device. The adsorbent bed comprises a metal-organic framework composite. In the method, one or more metal-organic frameworks in powder form are mixed in a liquid to produce a metal-organic framework suspension or other type of metal-organic framework coating, such as a suspension. A monolith is coated with the suspension or metal-organic framework coating to provide a metal-organic framework composite having at least one metal-organic framework coating layer deposited on and / or bordering the monolith. As described herein, the monolith can be two-dimensional or three-dimensional in shape. The produced metal-organic framework composite can be about 5 m in size. 2 / g~about 100m 2 / g and / or a relative BET surface area of ​​about 1% to about 10% relative to the metal-organic framework monolith, and a pore size of about 1 nm to about 50 nm.

[0026] The metal-organic frameworks disclosed herein may be characterized by their porosity. MOFs may contain micropores, mesopores, macropores, and any combination thereof. Micropores are defined herein as having a pore size of about 2 nm or less, and mesopores are defined herein as having a pore size of about 2 nm to about 50 nm. Intergranular porosity may be present in some cases.

[0027] Desirably, the metal-organic framework coatings and metal-organic framework composites produced according to the present methods retain at least a substantial portion of the BET surface area of ​​the pre-crystallized metal-organic framework powder from which they are formed. Specifically, these metal-organic framework composites can be characterized by a BET surface area of ​​about 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10% or more relative to the BET surface area of ​​the pre-crystallized metal-organic framework powder material.

[0028] As provided herein, the MOFs can be ZIFs (i.e., zeolitic imidazolate frameworks), MILs (i.e., Materioux de l'Institut Lavoisier), and IRMOFs (i.e., iso-reticular metal-organic frameworks), either alone or in combination with other MOFs. In certain embodiments, the MOFs are selected from HKUST-1, MOF-74, MIL-100, ZIF-7, ZIF-8, ZIF-90, UiO-66, UiO-67, MOF-808, or MOF-274.

[0029] MOFs can be prepared by combining organic ligands, i.e., one or a combination of two or more organic ligands, with a metal or metalloid, as described below. For example, MOF-274 is a metal complex consisting of Mg 2+ , Mn 2+ , Fe 2+ , Zn 2+ , Ni 2+ , Cu 2+ , Co 2+or a combination thereof with 4,4'-dihydroxy-(1,1'-biphenyl)-3,3'-dicarboxylic acid. Additionally, MOF-274 can contain amines that are coordinated to metal sites within its structure.

[0030] As used herein, "isotherm" refers to the adsorption of an adsorbate as a function of concentration while the temperature of the system is held constant. In an embodiment, the adsorbate is CO2 and the concentration can be measured as CO2 pressure. As described herein, isotherms can be performed by porous materials and using various mathematical models applied to calculate the apparent surface area. S. Brunauer, P. E. Metett, and E. Teller. J. Am. Chem. Soc. 1938, 60, 309-319; K. Walton and R. Q. Snurr, J. Am. Chem. Soc. 2007, 129, 8552-8556; I. Langmuir, J. Am. Chem. Soc. 1916, 38, 2221.

[0031] organic ligand As used herein, an organic ligand is a monodentate, bidentate or polydentate ligand. An organic ligand can be a single type of ligand or a combination thereof. In general, an organic ligand can be coordinated to a metal ion, and essentially any compound suitable for such coordination can be used. An organic ligand comprises at least two centers capable of coordinating a metal ion of a metal salt or a metal or metalloid. In an embodiment, an organic ligand comprises i) an alkyl group substructure having 1-10 carbon atoms, ii) an aryl group substructure having 1-5 aromatic rings, iii) an alkyl or arylamine substructure consisting of an alkyl group having 1-10 carbon atoms or an aryl group having 1-5 aromatic rings, the substructure having at least two functional groups "X" covalently bonded to the substructure, X being capable of coordinating to a metal or metalloid.

[0032] In embodiments, each X is independently selected from CO2H, OH, SH, NH2, CN, HCO, CS2H, NO2, SO3H, Si(OH)3, Ge(OH)3, Sn(OH)3, Sn(SH)3, PO3H, CH(RSH)2, C(RSH)3, CH(RNH2)2, C(RNH2)3, CH(ROH)2, C(ROH)3, CH(RCN)2, C(RCN)3, CH(SH)2, C(SH)3, CH(NH2)2, C(NH2)2, CH(OH)2, C(OH)3, CH(CN)2, C(CN)3, nitrogen-containing heterocycles, sulfur-containing heterocycles, and neutral or ionic forms thereof; and R is an alkyl group having 1 to 5 carbon atoms or an aryl group consisting of 1 to 2 phenyl rings.

[0033] In embodiments, the organic ligands include substituted or unsubstituted, mono- or polynuclear aromatic di-, tri-, and tetra-carboxylic acids and substituted or unsubstituted at least one heteroatom-containing aromatic di-, tri-, and tetra-carboxylic acids, which have one or more nuclei.

[0034] In embodiments, the organic ligand is benzenetricarboxylate (BTC) (one or more isomers), ADC (acetylene dicarboxylate), NDC (naphthalene dicarboxylate) (any isomer), BDC (benzene dicarboxylate) (any isomer), ATC (adamantane tetracarboxylate) (any isomer), BTB (benzene tribenzoate) (any isomer), MTB (methane tetrabenzoate), ATB (adamantane tribenzoate) (any isomer), biphenyl-4,4'-dicarboxylate, benzene-1,3,5-tris(1H-tetrazole), imidazole or derivatives thereof or combinations thereof.

[0035] Ligands with multidentate functional groups are H + , Na + , K + , Mg 2+ , Ca 2+ , Sr 2+, the corresponding counter cations such as ammonium ion, alkyl-substituted ammonium ion and aryl-substituted ammonium ion, or F - , Cl - , Br - , I - , ClO - , ClO2 - , ClO3 - , ClO4 - , O.H. - , NO3 - , NO2 - , SO4 2- , SO3 2- , PO4 3- , CO3 2- and HCO 3- and the like.

[0036] In an embodiment, the organic ligand comprises a monodentate functional group. A monodentate functional group is defined as a moiety attached to a substructure, which may comprise an organic ligand or amine ligand substructure L as defined above, that can form only one bond to a metal ion. In accordance with this definition, a ligand can contain one or more monodentate functional groups. For example, cyclohexylamine and 4,4'-bipyridine are ligands that contain monodentate functional groups, since each functional group can bond to only one metal ion.

[0037] Thus, cyclohexylamine is a monofunctional ligand containing a monodentate functional group, and 4,4'-bipyridine is a difunctional ligand containing two monodentate functional groups. Specific examples of ligands containing monodentate functional groups are pyridine (monofunctional ligand), hydroquinone (bifunctional ligand), and 1,3,5-tricyanobenzene (trifunctional ligand).

[0038] Ligands with monodentate functional groups can be blended with ligands containing polydentate functional groups to produce MOFs in the presence of suitable metal ions and, optionally, a templating agent. Monodentate ligands can also be used as templating agents. A templating agent can be added to the reaction mixture for the purpose of sealing pores in the resulting MOF. The monodentate ligands and / or templating agents can include the following substances and / or their derivatives: A. Alkyl or aryl amines or phosphines and their corresponding ammonium or phosphonium salts, the alkyl amines or phosphines can contain linear, branched or cyclic aliphatic groups (and their corresponding ammonium salts) having 1 to 20 carbon atoms, and the aryl amines or phosphines can contain 1 to 5 aromatic rings, including heterocycles. Examples of monofunctional amines are methylamine, ethylamine, n-propylamine, iso-propylamine, n-butylamine, sec-butylamine, iso-butylamine, tert-butylamine, n-pentylamine, neo-pentylamine, n-hexylamine, pyrrolidine, 3-pyrroline, piperidine, cyclohexylamine, morpholine, pyridine, pyrrole, aniline, quinoline, isoquinoline, 1-azaphenanthrene and 8-azaphenanthrene. Examples of di- and trifunctional amines are 1,4-diaminocyclohexane, 1,4-diaminobenzene, 4,4'-bipyridyl, imidazole, pyrazine, 1,3,5-triaminocyclohexane, 1,3,5-triazine and 1,3,5-triaminobenzene. B. Alcohols containing alkyl or cycloalkyl groups containing 1 to 20 carbon atoms or aryl groups containing 1 to 5 phenyl rings. Examples of monofunctional alcohols are methanol, ethanol, n-propanol, iso-propanol, allyl alcohol, n-butanol, iso-butanol, s-butanol, tert-butanol, n-pentanol, iso-pentanol, sec-pentanol, neo-pentanol, n-hexanol, cyclohexanol, phenol, benzyl alcohol and 2-phenylethanol. Examples of di- and trifunctional alcohols are 1,4-dihydroxycyclohexane, hydroquinone, catechol, resorcinol, 1,3,5-trihydroxybenzene and 1,3,5-trihydroxycyclohexane. C. Ethers containing an alkyl or cycloalkyl group containing 1 to 20 carbon atoms or an aryl group containing 1 to 5 phenyl rings. Examples of ethers are diethyl ether, furan and morpholine. D. Thiols containing an alkyl or cycloalkyl group containing 1 to 20 carbon atoms or an aryl group containing 1 to 5 phenyl rings. Examples of monofunctional thiols are thiomethane, thioethane, thiopropane, thiocyclohexane, thiophene, benzothiophene and thiobenzene. Examples of difunctional and trifunctional thiols are 1,4-dithiocyclohexane, 1,4-dithiobenzene, 1,3,5-trithiocyclohexane and 1,3,5-trithiobenzene. E. Nitriles containing alkyl or cycloalkyl groups containing 1 to 20 carbon atoms or aryl groups containing 1 to 5 phenyl rings. Examples of monofunctional nitriles are acetonitrile, propanenitrile, butanenitrile, n-valeronitrile, benzonitrile and p-tolunitrile. Examples of difunctional and trifunctional nitriles are 1,4-dinitrilocyclohexane, 1,4-dinitrilobenzene, 1,3,5-trinitrilocyclohexane and 1,3,5-trinitrilobenzene. F. Inorganic anions from the group consisting of sulfate, nitrate, nitrite, sulfite, bisulfite, phosphate, hydrogen phosphate, dihydrogen phosphate, diphosphate, triphosphate, phosphite, chloride, chlorate, bromide, bromate, iodide, iodate, carbonate, bicarbonate, thiocyanate and isonitrile, as well as the corresponding acids and salts of the aforementioned inorganic anions. G. Organic Acids and Corresponding Anions (and Salts). Organic acids can include alkyl organic acids containing linear, branched or cyclic aliphatic groups having 1-20 carbon atoms or aryl organic acids having 1-5 aromatic rings which may contain heterocycles, and their corresponding aryl organic anions and salts. H. Other organic and inorganic substances such as ammonia, carbon dioxide, methane, oxygen, ethylene, hexane, benzene, toluene, xylene, chlorobenzene, nitrobenzene, naphthalene, naphthalene, thiophene, pyridine, acetone, 1-2-dichloroethane, methylene chloride, tetrahydrofuran, ethanolamine, triethylamine or trifluoromethylsulfonic acid.

[0039] Additionally, templating agents can include other aliphatic and aromatic hydrocarbons that do not contain functional groups. In embodiments, templating agents include cycloalkanes, such as cyclohexane, adamantane, or norbornene, and / or aromatic compounds, such as benzene, toluene, or xylene.

[0040] Metal ions As described above, MOFs can be synthesized by combining metal ions, organic ligands, and optionally a suitable templating agent. Suitable metal ions include metals and metalloids in various coordination structures and oxidation states. In embodiments, MOFs are produced using metal ions with distinctly different coordination structures in combination with ligands with multidentate functional groups and a suitable templating agent. MOFs can be prepared using metal ions that favor octahedral coordination, such as cobalt(II), and / or metal ions that favor tetrahedral coordination, such as zinc(II). MOFs can be synthesized using the following metal ions: Mg 2+ , Ca 2+、Sr 2+ ,Bar 2+ 、Sc 3+ 、Y 3+ ,Tea 4+ 、Zr 4+ 、Hf 4+ 、V 5+ 、V 4+ 、V 3+ 、V 2+ 、Nb 3+ ,Pitch 3+ 、Cr 3+ 、Mo 3+ 、W 3+ 、Mn 3+ 、Mn 2+ 、Re 3+ 、Re 2+ 、Fe 3+ 、Fe 2+ 、Ru 3+ 、Ru 2+ ,Home 3+ ,Home 2+ 、Co 3+ 、Co 2+ 、Rh 2+ 、Rh + 、Ir 2+ 、Ir + ,Knee 2+ ,Knee + 、Pd 2+ 、Pd + 、Pt 2+ 、Pt + 、Cu 2+ 、Cu + 、Ag + 、Au + 、Zn 2+ 、Cd 2+ 、Hg 2+ 、Al 3+ 、Ga 3+ ,His 3+ 、Tl 3+ ,See 4+ ,See 2+ 、Ge 4+ 、Ge 2+ 、Sn 4+ 、Sn 2+ 、Pb 4+ 、Pb 2+ ,As 5+ ,As 3+ ,As + 、Sb 5+ 、Sb 3+ 、Sb +and Bi 5+ , Bi 3+ , Bi + , B.E. 2+ The term metal ion refers to both metal ions and metalloid ions. In embodiments, metal ions suitable for use in the preparation of MOFs include, in combination with the counter anion of the corresponding metal salt, Sc 3+ , Ti 4+ , V 4+ , V 3+ , V 2+ , Cr 3+ , Mo 3+ , Mg 2+ , Mn 3+ , Mn 2+ , Fe 3+ , Fe 2+ , Ru 3+ , Ru 2+ , Os 3+ , Os 2+ , Co 3+ , Co 2+ , Rh 2+ , Rh + , Ir 2+ , Ir + , Ni 2+ , Ni + , Pd 2+ , Pd + , Pt 2+ , Pt + , Cu 2+ , Cu + , Ag + , Au + , Zn 2+ , Cd 2+ , Al 3+ , Ga 3+ , In 3+ , Ge 4+ , Ge 2+ , Sn 4+ , Sn 2+ , Pb 4+ , Pb 2+ , Sb 5+ , Sb 3+ , Sb + and / or Bi 5+ , Bi 3+ , Bi + , B.E. 2+In embodiments, the metal ions for use in the preparation of MOFs may include, along with the counter ion of the corresponding metal salt, Sc 3+ ,Ti 4+ , V 4+ , V 3+ , Cr 3+ , Mo 3+ , Mn 3+ , Mn 2+ , Fe 3+ , Fe 2+ , Co 3+ , Co 2+ , Ni 2+ , Ni + , Cu 2+ , Cu + , Ag + , Zn 2+ , Cd 2+ , Al 3+ , Sn 4+ , Sn 2+ and / or Bi 5+ , Bi 3+ , Bi + In embodiments, the metal ion for use in the preparation of the MOF includes Mg, along with the counterion of the corresponding metal salt. 2+ , Mn 3+ , Mn 2+ , Fe 3+ , Fe 2+ , Co 3+ , Co 2+ , Ni 2+ , Ni + , Cu 2+ , Cu + , Pt 2+ , Ag + and Zn 2+ is selected from the group consisting of:

[0041] Preparation of metal-organic frameworks The synthesis of rigid and stable metal-organic frameworks ("MOFs") can be carried out under very mild reaction conditions. Often, the reagents are combined in solution, either aqueous or non-aqueous, and the synthesis reaction temperature ranges from 0°C to 100°C (in an open beaker). In other cases, solution reactions are carried out in closed vessels at temperatures between 25°C and 300°C. In either case, large single crystals or microcrystalline microporous solids are formed.

[0042] In the preparation of MOFs, reactants can be added in a molar ratio of metal ions to ligands containing multidentate functional groups of 1:10 to 10:1. In embodiments, the ratio of metal ions to ligands containing multidentate functional groups is 1:3 to 3:1, such as 1:2 to 2:1. The amount of templating agent can affect the preparation of MOFs, i.e., the templating agent can be used in certain circumstances as a solvent in which the reaction occurs. Thus, the templating agent can be used in great excess without interfering with the reaction and preparation of MOFs. Furthermore, when a ligand containing monodentate functional groups is used in combination with a metal ion and a ligand containing multidentate functional groups, the ligand containing monodentate functional groups can be utilized in excess. In certain circumstances the ligand containing monodentate functional groups can be used as a solvent in which the reaction occurs. Furthermore, in certain circumstances the templating agent and the ligand containing monodentate functional groups can be the same. An example of a templating agent that is a ligand containing monodentate functional groups is pyridine.

[0043] The preparation of MOFs can be carried out in either aqueous or non-aqueous systems. The solvent can be polar or non-polar, and the solvent can be a templating agent or an optional ligand containing a monodentate functional group. Examples of non-aqueous solvents include n-alkanes such as pentane, hexane, benzene, toluene, xylene, chlorobenzene, nitrobenzene, cyanobenzene, aniline, naphthalene, naphthalene, naphtha, n-alcohols such as methanol, ethanol, n-propanol, isopropanol, acetone, 1,2,-dichloroethane, methylene chloride, chloroform, carbon tetrachloride, tetrahydrofuran, dimethylformamide, dimethylsulfoxide, thiophene, pyridine, ethanolamine, triethylamine, ethylenediamine, etc.

[0044] To form large single crystals of microporous materials suitable for single crystal x-ray structural characterization, the solution reaction can be carried out in the presence of viscous materials such as polymer additives. Specific additives can include polyethylene oxide, polymethylmethacrylate, silica gel, agar, fat, and collagen, which can facilitate achieving high yields and high purity crystalline products. The growth of large single crystals of microporous materials provides unambiguous characterization of the microporous structure. Large single crystals of microporous materials can be useful for magnetic and electronic sensing applications.

[0045] This method A method of producing an adsorbent bed comprising the steps of: (a) mixing a metal-organic framework in powder form in a liquid to produce a suspension; (b) providing a monolith; (c) dip-coating the monolith in the colloidal suspension to produce a metal-organic framework composite having at least one metal-organic framework coating layer deposited on and bordering the monolith; and (d) drying the metal-organic framework composite to produce a monolith having a thickness of about 1 m. 2 / g~about 300m 2 and producing an absorbent bed having a BET surface area of ​​about 100 nm to about 50 nm.

[0046] As described herein, the step of mixing the metal-organic framework with a liquid can produce a suspension or colloidal suspension that is useful when applying a metal-organic framework coating layer onto a monolith. The coating is then applied to the monolith by dip coating, wash coating, or solvothermal deposition to produce a metal-organic framework composite having at least one metal-organic framework coating layer deposited on the monolith. The monolith can be coated with multiple layers of the same or different metal-organic frameworks to provide a composite that is particularly useful as an adsorbent bed and a microreactor. In addition to coating the monolith, coating a planar substrate with the suspension can be useful when producing high surface area supports or rolled-up foils.

[0047] More specifically, the method may also include the steps of: (a) mixing a metal-organic framework in powder form in a liquid to produce a colloidal suspension; (b) providing a monolith; (c) dip-coating the monolith in the colloidal suspension to produce a metal-organic framework composite having at least one metal-organic framework coating layer deposited on and bordering the monolith; and (d) drying the metal-organic framework composite to produce an absorbent bed having a relative BET surface area of ​​about 40% to about 100% relative to the metal-organic framework monolith and a pore size of about 1 nm to about 50 nm.

[0048] To apply the coating onto the monolith by wash coating, the metal-organic framework powder is mixed into a liquid to produce a suspension. The metal-organic framework powder is about 10% to about 90% by weight, about 20% to about 80% by weight, about 25% to about 75% by weight, and / or about 30% to about 50% by weight of the suspension, and the suspension is acid-free. The suspension is cast onto a substrate to produce a metal-organic framework composite having a metal-organic framework coating layer deposited on the monolith. The metal-organic framework composite can then be heated with one or more zeolites to attach the metal-organic framework coating to the monolith. The resulting metal-organic framework composite can be washed with water to produce a solution of about 5m 2 / g~about 100m 2 / g or 1m 2 / g~about 300m 2 / g and / or a relative BET surface area of ​​about 40% to about 100% relative to the metal-organic structure monolith, and has a pore size of about 1 nm to about 50 nm.

[0049] Additionally, metal-organic framework composites can be fabricated by thermal deposition, where a metal-organic framework powder is mixed with a liquid to form a metal-organic framework coating. The metal-organic framework coating is then applied to the monolith by thermal deposition to fabricate the metal-organic framework composite. The metal-organic framework coating comprises a weight percent (wt%) of the metal-organic framework in a liquid ranging from about 30 wt% to about 60 wt%.

[0050] Optionally, in any of the methods described herein, the metal-organic framework complex is heated to about 250° C. o F to produce the metal-organic framework complex.

[0051] In an embodiment, the metal-organic framework is HKUST-1, the liquid is ethanol, and the monolith is alumina washcoated cordierite. In an embodiment, the metal-organic framework is Mg-MOF-74, the liquid is ethanol, and the monolith is ceramic. In an embodiment, the method further comprises aging the metal-organic framework composite at a temperature between about 40° C. and about 150° C. for a period of about 30 minutes or more. In an embodiment, the method further comprises calcining the metal-organic framework composite at a temperature between about 100° C. and about 300° C. for a period of about 1 hour or more.

[0052] In an embodiment, the method further comprises washing the metal-organic framework complex with an optional solvent. In an embodiment, the optional solvent is selected from the group of water, methanol, ethanol, N,N-dimethylformamide, acetone, diethyl ether, acetonitrile, ketones, amides, esters, ethers, nitriles, aromatic hydrocarbons, aliphatic hydrocarbons, and combinations thereof. In an embodiment, the adsorbent bed is a channel reactor for gases and fluids.

[0053] In an embodiment, the monolith is selected from the group of ceramic, metal, polymeric substrate, and / or cellulose fiber. In an embodiment, the monolith is ceramic. In an embodiment, the polymeric substrate comprises polyvinylamide, polyacrylate, polymethacrylate, polycarbonate, polyamide, polyester, polyether, polyvinylamine, polyvinyl alcohol, poly(vinyl ester), polyamide, poly(amic acid), and / or combinations thereof. In an embodiment, the liquid comprises polyvinyl acetate and water, and the ratio of polyvinyl acetate to water is about 1:1 to about 1:3.

[0054] In an embodiment, the metal-organic framework is selected from the group of HKUST-1, UiO-66, ZIF-8, ZIF-7, MIL-100, MOF-74, M2(m-dobdc), MOF-274, Cu(Qc)2, and combinations thereof.

[0055] Deposited on and / or bordering the monolith, approximately 5 m 2 / g~about 100m 2 Further provided herein is a channel reactor for gases and fluids comprising one or more layers of a metal-organic framework coating that results in a metal-organic framework composite having a BET surface area of ​​about 100 nm / g and / or a relative BET surface area of ​​about 1% to about 10% relative to the metal-organic framework monolith and a pore size of about 1 nm to about 50 nm. In an embodiment, the monolith of the channel reactor is cordierite. In an embodiment, the cordierite is washcoated with alumina.

[0056] Monolith The monolith can be a substrate for a monolithic or honeycomb structure. The monolith can be made of a single type of material or different materials, such materials can include ceramics, metals, or can be polymeric substrates or cellulose fibers. For example, the monolith can include one or more of the following ceramics: cordierite, alumina, cordierite-alpha alumina, silicon nitride, zircon mullite, spodumene, alumina-silica magnesia, zircon silicate, sillimanite, magnesium silicate, zircon, petalite, aluminosilicate, and combinations thereof. In an embodiment, the ceramic monolith is made of cordierite, alumina, or combinations thereof.

[0057] The monolith may comprise aluminum, titanium, stainless steel, Fe-Cr alloy, or Cr-Al-Fe alloy in the form of a sheet, mesh, foil, flake, powder, wire, rod, or combinations thereof. In an embodiment, the monolith comprises aluminum, stainless steel, Cr-Al-Fe alloy, or combinations thereof in the form of a sheet, mesh, or foil. In an embodiment, the monolith comprises about 80% to about 97% by weight alumina blended with about 1% to about 10% by weight silica and / or about 1% to about 5% by weight of an oxide selected from the group of silica, titania, magnesia, and calcium oxide.

[0058] The monoliths can include polyolefins, polyesters, polyurethanes, polycarbonates, polyetheretherketones, polyphenylene oxides, polyethersulfones, melamines, polyamides, polyacrylates, polystyrenes, polyacrylonitriles, polyimides, polyfurfural alcohol, phenol furfuryl alcohol, melamine formaldehyde, resorcinol formaldehyde, cresol formaldehyde, phenol formaldehyde, polyvinyl alcohol dialdehyde, polycyanurates, polyacrylamides, various epoxy polymers and / or copolymers, agar and agarose, or combinations thereof. In embodiments, the plastic monoliths can be made from polyolefin, polyester, polyurethane, melamine, polypropylene, or polyamide polymers and / or copolymers.

[0059] The monolith can include cellulose fibers (i.e., paper). The monolith can be ceramic pellets or carbon pellets. The monolith can be a planar substrate or a substrate made by layering corrugated metal foil and corrugated plastic sheets, respectively.

[0060] The choice of monolith will depend on the desired properties of the monolith composite. For example, in applications where reduced system weight is important or where pressure drop is important, metal and cellulose fiber honeycombs may offer advantages over ceramic honeycombs. In applications where heat transfer is important, metal honeycombs may offer advantages over ceramics.

[0061] Polymer Binder The metal-organic framework coating layer may optionally include one or more polymeric binders. The polymeric binders may be polar or non-polar polymers, such as homopolymers and copolymers of esters, amides, acetates, anhydrides, imides, ethers, amic acids, vinyls, acrylics, ethylene, and / or propylene, and / or butenes, C2-C6, C8, C9, C10, C11, C12, C13, C14, C15, C16, C17, C18, C19, C20, C21, C22, C30, C40, C50, C61, C72, C83, C94, C95, C96, C97, C98, C99, C101, C112, C123, C134, C142, C146, C156, C167, C168, C179, C181, C182, C183, C184, C185, C186, C187, C188, C189, C191, C192, C193, C194, C195, C196, C197, C198, C199, C201, C202, C203, C204, C205, C206, C207, C208, C209, C301, C302, C303, C304, C305, C306, C307, C308, C309, C410, C420, C430, C440, C450, C451, C460, C470, C480, C491, C492, C493, C494, C495, C496, C4 20 Copolymers of olefins and one or more polar monomers, such as acetates, anhydrides, esters, alcohols, and / or acrylics, may be included. Further examples of polymeric binders include polyesters, polyamides, ethylene vinyl acetate copolymers, polyvinyl chloride, polyvinyl alcohol (PVA), polyvinyl acetate, mixtures of polyvinyl alcohol and acetate, polyvinyl amines, polycellulose ethers, or derivatives thereof. In embodiments, the polymeric binder includes polyvinyl alcohol or derivatives thereof, such as polyvinyl alcohol, polyvinyl acetate, polyvinyl butyrate, or polyvinyl propionate.

[0062] The polymeric binder may be selected from the group consisting of polyethylene, polypropylene, polyolefin copolymers, polyisoprene, isoprene rubber, polybutadiene, polybutadiene copolymers, chlorinated rubber, nitrile rubber, polychloroprene, chloroprene rubber, ethylene-propylene-diene elastomers, polystyrene, polyacrylates, polymethacrylates, polyacrylonitrile, poly(vinyl esters), poly(vinyl halides), polyamides, cellulose polymers, polyimides, acrylics, vinyl acrylics and styrene acrylics, polyvinyl alcohol, thermoplastic polyesters, thermosetting polyesters, fluorinated polymers such as poly(phenylene oxide), poly(phenylene sulfide), poly(tetrafluoroethylene) polyvinylidene fluoride, poly(vinyl fluoride) and chloro / fluoro copolymers such as ethylene chlorotrifluoro-ethylene copolymer, polyamides, phenolic resins and epoxy resins, polyurethanes, silicone polymers and combinations thereof.

[0063] In an embodiment, the polymeric binder is a polymer blend of two or more polymers. The polymeric binder can contain a mixture of polymers where a first polymer is present in a weight percent (wt%) ranging from about 10% to about 99% by weight of the polymer mixture, such as 20% to 95%, 30% to 90%, 40% to 90%, or 50% to 90% by weight, with the remainder of the weight being a second polymer or combination of polymers. In an embodiment, the polymeric binder comprises a polymer blend of polyvinyl alcohol and polyvinyl acetate.

[0064] Optional Additives Additionally, the metal-organic framework coating layer may contain, for example, fillers, antioxidants (e.g., IRGANOX, available from Ciba-Geigy), and / or other additives. TM 1010 or IRGANOX TMhindered phenols such as 1076, photo-oxidation inhibitors (e.g., hindered amine light stabilizers such as TINUVN® 123 available from BASF, HALS, phosphites (e.g., IRGAFOS® available from Ciba-Geigy, TM 168), antiblocking additives, tackifiers, such as polybutene, terpene resins, aliphatic and aromatic hydrocarbon resins, alkali metal and glycerol stearates, and hydrogenated rosins, ultraviolet stabilizers, heat stabilizers, antiblocking agents, release agents, antistatic agents, pigments, colorants, dyes, waxes, silicas, fillers, and talc.

[0065] Other optional additives include silicas such as precipitated silica and silicas derived from by-products such as fly ash, e.g., silica-alumina, silica-calcium particles, or fumed silica. In an embodiment, the silica is a particulate material and has an average particle size of 10 μm or less, e.g., an average particle size of 5 μm or less, or 1 μm or less. In an embodiment, the silica is amorphous silica.

[0066] Other additives that may be optionally included in the organometallic coating layer include inorganic compounds such as titanium dioxide, hydrated titanium dioxide, hydrated alumina or alumina derivatives, mixtures of silicon and aluminum compounds, silicon compounds, clay minerals, alkoxysilanes, and amphiphiles. The additives may also include any suitable compound used for the deposition of powdered materials, such as oxides of silicon, aluminum, boron, phosphorus, zirconium, and / or titanium. In addition, the additives may include oxides of magnesium and beryllium. In addition, tetraalkoxysilanes, such as tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane, similar tetraalkoxytitanium and tetraalkoxyzirconium compounds, and trimethoxy-, triethoxy-, tripropoxy-, and tributoxy-aluminum, may be used as additives.

[0067] Suspension As described above, the method includes mixing and / or suspending the metal-organic framework in a liquid suspension. In the method, the metal-organic framework remains dispersed in the liquid. Preferred organic solvents include ethanol, methanol, DMF (dimethylformamide) and water. In embodiments, the solvent may be a mixture of two or more organic solvents. The suspension may be in the form of a liquid or a gas.

[0068] The weight percentage of the metal-organic framework to the organic solvent is variable for each metal-organic framework. The various weight percentages of the MOF to the organic solvent depend on the particle size, solvent solubility, pore volume, viscosity, and colloidal stability of the metal-organic framework in the liquid. The suspension can have a pH of about 5 to about 9, or about 6 to about 8.

[0069] The MOF composite with the metal-organic framework layer can optionally undergo aging, such as drying or settling of the MOF composite. The drying temperature cannot exceed 250°F and can be from about 5°F to about 250°F, from about 20°F to about 200°F, or from about 20°F to about 150°F. The aging can be carried out for a time period of from about 1 minute to about 72 hours, such as from about 30 minutes to about 72 hours, from about 1 hour to about 48 hours, or from about 1 hour to about 24 hours. In an embodiment, the aging can be carried out in air or in humidified air at 20% to 100% relative humidity, such as 70% to 100%. Treatment with humidified gas can allow hydration of the material, which can be advantageous for curing certain polymer binders. In an embodiment, the aging can be carried out in dehumidified air or inert gas, such as in air at 0% to 10% relative humidity or 0% to 5% relative humidity.

[0070] The MOF composite can optionally undergo activation. Activation can be carried out at a temperature of about 50°F to about 250°F. Activation can be carried out for a time period of about 1 hour ("h") to about 6h, such as about 1h to about 4h. Activation can facilitate removal of the solvent. Activation can be carried out in a mixture containing air, an inert gas, or oxygen. Additionally, activation can be carried out at reduced or increased pressure, such as in a vacuum or at a pressure higher than atmospheric pressure.

[0071] In embodiments, the MOF composites can be calcined under dry air or air with different levels of humidity, or they are heat treated in the presence of a gas mixture containing an inert gas, such as nitrogen and / or oxygen. In embodiments, the gas mixture used can contain 5% or more by volume of oxygen, such as 10% or more by volume. In embodiments, the gas mixture contains no or substantially no oxygen, and only inert gases. Calcination temperatures can be from about 50°C to about 250°F.

[0072] Properties of MOF composites The MOF composite prepared by this method has a diameter of about 5 m 2 / g~about 200m 2 / g, approx. 5m 2 / g~about 150m 2 / g, approx. 5m 2 / g~about 100m 2 / g, approx. 5m 2 / g ~ approx. 75m 2 / g, about 20m 2 / g~about 100m 2 / g, approx. 40m 2 / g~about 100m 2 / g, about 20m 2 / g~about 80m 2 / g or about 30m 2 / g~about 70m 2 / g (measured using ASTM D3663).

[0073] Additionally, the MOF composites prepared by the present methods can have a relative BET surface area (measured using ASTM D3663) of about 1% to about 10% of the pure MOF, such as about 1% to about 9% or about 2% to about 8%.

[0074] The MOF-coated MOF composites prepared by the present methods can have an average pore width (measured using ASTM D4365) of about 1 nm to about 2.5 nm, about 1 nm to about 2.2 nm, about 1 nm to about 2 nm, about 1.2 nm to about 2.5 nm, about 1.5 nm to about 2.5 nm, or about 1.5 nm to about 2 nm.

[0075] The MOF composite comprises about 1% to 10%, 2% to 8%, or 3% to 6% by weight of the metal-organic framework. In any embodiment, the MOF composite can comprise 3.15%, 4.5%, or 6.1% by weight of the metal-organic framework.

[0076] Purpose The present metal-organic framework composites are useful in any application where a porous or channeled body offers advantages over a solid or powder and where the operating temperature does not exceed 400° C. and the operating pressure does not exceed 150 bar. In particular, these applications may include, but are not limited to, channel reactors, adsorption beds, desiccants or other fluid storage, ion exchangers, and molecular sieves.

[0077] Furthermore, MOF composites can be used to catalyze a variety of reactions, where the presence of channels and / or pores introduced therein is known or believed to increase the activity and / or selectivity and / or yield of the reaction.

[0078] Another application is the storage of chemical compounds, especially gaseous compounds. The pore size and porosity of MOF composites can allow for excellent storage or sequestration of gaseous compounds such as CO2, CH4 or H2, as well as separation of gases, all of which are particularly important in the energy industry.

[0079] Features of the present invention are illustrated in the following non-limiting examples. EXAMPLES

[0080] The coating of cordierite monoliths was completed by dip-coating them in a suspension of metal-organic frameworks (MOFs). Two metal-organic frameworks were used: HKUST-1 (Cu3(btc)2; btc3- = 1,3,5-benzenetricarboxylate); and Mg-MOF-74 (Mg2(dobdc); dobdc4- = 2,5-dihydroxy-1,4-benzenedicarboxylate). The suspension for HKUST-1 coating was prepared by suspending HKUST-1 powder in ethanol (40 wt% HKUST-1 in ethanol). The monoliths used were 1 inch with 400 channels per square inch ("CPSI") and 55% OFA. The monoliths were dip-coated twice, with a drying step after each dip-coating step, to achieve the metal-organic framework monoliths with HKUST-1 coating layer shown in Figure 1A and Figure 1B. The HKUST-1 metal-organic framework coating is shown in blue in these figures. The figures further show a relatively uniform thickness throughout the monolith. As shown, the monolith has square shaped channels with the thickness layering at right angles to the channels, and the channels become "rounder" after dip coating.

[0081] A suspension for dip-coating HKUST-1 was prepared by suspending HKUST-1 powder in ethanol (40 wt % HKUST-1 in ethanol). The Brunauer-Emmett-Teller surface area (referred to herein as the "BET surface area") of the metal-organic framework composite was 42 m. 2 / g, which includes the mass of the monolith itself. The monolith itself has no significant surface area, so the observed surface area of ​​the metal-organic framework composite can be attributed entirely to the MOF coating. The BET surface area of ​​the MOF, HKUST-1, is approximately 1500 m 2 / g. The metal-organic framework coating was 6.1% of the total metal-organic framework composite mass. Given the BET of the high purity metal-organic framework, the predicted BET surface area is 92 m for the composite. 2 / g, and the metal-organic framework is experimentally found to be 42m 2 / g. Furthermore, the pore size calculated from the N2 isotherm shows that the average pore width of the monolith composite is 1.697 nm, which is the pore width of the metal-organic framework HKUST-1, indicating that the porosity comes from the metal-organic framework HKUST-1 and is maintained in the present methodology.

[0082] A coating of metal-organic framework HKUST-1 in ethanol was also dip-coated onto an alumina monolith with square channels and 400 channels / in 2 . The monolith was 26 m 2 The metal-organic framework composite had a BET surface area of ​​1.01 m / g and an average pore width of 1.622 nm, again consistent with the HKUST-1 coating on the monolith. The metal-organic framework composite yielded 4.5 wt. % HKUST-1, which was 67 m 2 / g, again close to the experimentally obtained value.

[0083] Further dip-coating experiments were carried out using a different monolith containing Mg-MOF-74 coated onto an applied ceramic monolith, and Figure 2 shows a micrograph of the organometallic composite.

[0084] Figure 3 shows the two monoliths before coating. The color change and thickness change of the monoliths compared to the above image of the coated monoliths indicates the success of the organometallic coating.

Claims

1. 1. A method for producing a metal-organic framework composite, comprising: mixing the metal-organic framework with a liquid to produce a suspension, the liquid being ethanol; applying said suspension to a monolith by dip coating, wash coating or solvothermal deposition to produce a metal-organic framework composite having at least one metal-organic framework coating layer deposited on said monolith; drying said composite metal-organic framework to produce said composite metal-organic framework having a BET surface area of ​​5 m 2 / g to 100 m 2 / g and / or a relative BET surface area of ​​1% to 10% of that of the pure metal-organic framework and a pore size of 1 nm to 50 nm; The method includes:

2. mixing said metal-organic framework in powder form into said liquid to produce a colloidal suspension; Providing the monolith; dip coating said monolith in said colloidal suspension to produce a metal-organic framework composite having at least one metal-organic framework coating layer deposited on and bordering said monolith; The metal-organic framework composite is dried and then dried for 5 m. 2 / g to 100m 2 producing said metal-organic framework composite having a BET surface area of ​​100 / g; The method of claim 1 , comprising:

3. mixing said metal-organic framework in powder form into said liquid to produce a colloidal suspension; Providing the monolith; dip coating said monolith in said colloidal suspension to produce a metal-organic framework composite having at least one metal-organic framework coating layer deposited on and bordering said monolith; drying said composite metal-organic framework to produce an absorbent bed and / or a microreactor having a relative BET surface area of ​​1% to 10% of that of said pure metal-organic framework; 13. The method of claim 1 for producing an adsorbent bed and / or a microreactor comprising:

4. The metal-organic framework complex is useful as an adsorbent bed, and the method comprises: suspending a metal-organic framework powder in the liquid to produce a suspension, the metal-organic framework powder being 10% to 90% by weight of the suspension, and the suspension being acid-free; flowing the suspension over the monolith to produce a metal-organic framework composite comprising a metal-organic framework coating deposited on the monolith; heating said metal-organic framework composite with one or more zeolites to adhere said metal-organic framework coating to said monolith; The method of claim 1 , comprising:

5. mixing a metal-organic framework powder with the liquid to form a metal-organic framework coating; applying said metal-organic framework coating to said monolith by thermal deposition to produce a metal-organic framework composite, said metal-organic framework coating comprising a weight percent of said metal-organic framework in said liquid ranging from 30 wt % to 60 wt %; drying the metal-organic framework composite at a temperature less than 250° C. to produce the metal-organic framework composite; The method of claim 1 , comprising:

6. The metal-organic framework complex has a length of 5 m 2 / g to 100m 2 The method of claim 5, wherein the SiO2 has a BET surface area of ​​100 / g.

7. The method according to any one of claims 1 to 6, wherein the monolith is selected from the group of ceramics, metals, polymeric substrates and / or cellulose fibres.

8. The method of any one of claims 1 to 7, wherein the monolith is ceramic.

9. The method of any one of claims 1 to 8, wherein the polymeric substrate comprises polyvinylamide, polyacrylate, polycarbonate, polyamide, polyester, polyether, polyvinylamine, polyvinyl alcohol, polyvinyl ester and / or combinations thereof.

10. The method of any one of claims 1 to 9, wherein the metal-organic framework is HKUST-1 and the monolith comprises alumina.

11. The method of any one of claims 1 to 10, wherein the metal-organic framework is Mg-MOF-74 and the monolith is ceramic.

12. The metal-organic frameworks include HKUST-1, UiO-66, ZIF-8, ZIF-7, MIL-100, MOF-74, M 2 (m-dobdc), MOF-274, Cu(Qc) 2 The method of any one of claims 1 to 11, wherein the compound is selected from the group consisting of:

13. The method of any one of claims 1 to 12, further comprising aging the metal-organic framework complex at a temperature between 40°C and 150°C for a period of 30 minutes or more.

14. The method of any one of claims 1 to 13, further comprising heat treating the metal-organic framework composite at a temperature between 100°C and 300°C for a period of one hour or more.

15. The method of any one of claims 1 to 14, further comprising washing the metal-organic framework complex with an optional solvent.

16. 16. The method of claim 15, wherein the optional solvent is selected from the group of water, methanol, ethanol, dimethylformamide, acetone, diethyl ether, acetonitrile, ketones, amides, esters, ethers, nitriles, aromatic hydrocarbons, aliphatic hydrocarbons, and combinations thereof.

17. A method according to any one of the preceding claims, wherein the suspension comprises from 20% to 70% by weight of solids, based on the total weight of the suspension.

18. The method according to any one of claims 1 to 17, wherein the composite is an absorbent bed or a channel reactor for gases and fluids.

19. 19. The method according to any one of claims 1 to 18, wherein the monolith comprises 80% to 97% by weight of alumina blended with 1% to 10% by weight of silica and / or 1% to 5% by weight of an oxide selected from the group of silica, titania, magnesia and calcium oxide.

20. 1. A channel reactor for gases and fluids comprising at least one layer of a metal-organic framework coating deposited on and bordering a monolith resulting in a metal-organic framework composite, said metal-organic framework composite having a length of 5 m 2 / g to 100m 2 / g BET surface area and / or a relative BET surface area of ​​1% to 10% of that of the pure metal-organic framework and a pore size of 1 nm to 50 nm.

21. 21. The channel reactor of claim 20, wherein the monolith is cordierite.

22. 22. The channel reactor of claim 21 , wherein the monolith comprises alumina.

Citation Information

Patent Citations

  • Regular-structure adsorbing material preparation, adsorbing material and application

    CN106807330A

  • Formed body containing a metal-organic framework

    JP2005528204A

  • Use and apparatus of porous crystalline solid mixtures as nitrogen oxide reduction catalysts

    JP2012527995A

  • Molded body, and production method of the same

    JP2019056055A

  • Noble gas separation membrane and method using the same for manufacturing noble gas with practically applicable purity

    JP2019118859A